Struktur Vegetasi Habitat Tumbuhan Endemik Begonia kelimutuensis di Taman Nasional Kelimutu - Yosephina Payu Wao; Melania Priska; Natalia Peni (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
Begonia kelimutuensis is an endemic species of Kelimutu National Park, Ende Regency, East Nusa Tenggara. Since it was designated as an endemic plant, this species has become one of the attractions for visitors to the Kelimutu National Park. However, research studies on this species are not widely known, so further research is needed. This study aims to determine the structure of the vegetation, the composition of plant species in the habitat of Begonia kelimutuensis and the Important Value Index (INP). The research method used is the plotted line method, with 20m x 20m plots used to collect tree species data, 10m x 10m plots used to collect pole type data, 5m x 5m sample plots used to collect sapling type data, and sample plots The size of 2m x 2m was used to collect data on the type of seedling with a distance between plots of 20m, which was placed along the observation path. Data analysis was carried out using the vegetation analysis method that calculates frequency, density, dominance, relative frequency, relative density, relative dominance, and Important Value Index (INP). The results showed that the composition of tree species in this area consisted of 44 species with a vegetation structure consisting of trees, poles, saplings and seedlings. The highest INP at the seedling level was Suregada sp. by 72.33%; at the sapling level is Suregada sp. by 83.86%; at the pole level is Chyathea contaminans of 79.15%; and at the tree level is Schfflera lucida by 58, 33%.